Continued Remuneration in the Event of Illness in Germany: Actual Costs for Manufacturing Companies - Ralf STAHLBERG (Communications of International Proceedings, 2021)
The continued remuneration system as it exists in Germany, or rather the German-speaking countries, is an exemplary social safeguard for employees to protect them from financial problems in the event of illness. However, the actual costs that arise in connection with the continued remuneration in companies are not transparent and lead to a considerable burden for companies, especially in connection with the duration of the continued remuneration. In this article, the actual costs that arise due to incapacity to work in companies are presented, explained and attention is drawn to related risks.
Keywords: Continued remuneration; incapacity for work; lateral absenteeism costs (LAC); labor cost